ANTECEDENTS OF WORK PERFORMANCE IN THE INDUSTRY AND ORGANIZATIONS REALM IN INDONESIA - Marhaenis, Angelo Basario (Transpublika Publisher, 2024)
Work performance is a critical factor that employees can enhance through a strong sense of responsibility towards their duties. Evaluating employee job accountability involves assessing their work performance as a measure of their contributions and achievements within the company. This research aims to provide an overview of antecedents of work performance from an industrial and organizational psychology perspective. Conducted from September 2022, the literature review applied strict inclusion and exclusion criteria, analyzing 10 selected articles. Employee work performance thrives on positive stimuli that mitigate stress and motivate improved job performance. A significant finding highlights the role of positive stimuli, such as rewards, recognition, and growth opportunities, in enhancing employee performance. When employees feel valued and appreciated, they exhibit higher motivation and engagement, leading to enhanced overall performance.